CAPACIDADE GERMINATIVA E QUALIDADE DE MUDAS DE Jacaranda micrantha PROVENIENTES DE FRAGMENTOS URBANO, PERIURBANO E RURAL DA FLORESTA OMBRÓFILA MISTA - Sanson, Daniela (2019)
This work aimed to obtain information about the germination process and quality of Jacaranda micrantha seedlings produced with seeds from forest fragments in the urban-rural gradient. Thus, we divided the present work into three parts, i) biometric characterization of fruits and seeds; (ii) evaluation of the potential of seed germination; iii) quality evaluation of seedlings. In order to evaluate the germination process potential, we tested seeds from different forest fragments (urban, periurban and rural), different germination environments (BOD, greenhouse and shade house), different time of imbibition (0, 12, 24, 48 hours) and different light intensities (5, 25, 50 and 100%). The evaluation of seedlings quality was carried out by comparing seeds from three different forest fragments by means of the evaluation of its characteristics as shoot height (H), collar diameter (DC), H / D ratio, above ground dry mass (MSPA) and root dry mass (MSR). Fruits and seeds of J. micrantha showed biometric variability among forest fragments, with the highest means for the periurban fragment. In general, the germination process started on the 10th day and finished on the 48th day. We observed a significant difference among seeds performance according to the forest fragment where we collected them. Seeds from the urban fragment showed the worst vigor when compared to seeds from the periurban and rural fragments. The greenhouse was the best environment because provided the best uniform germination for the species. We verified that the seeds of J. micrantha have good potential for germination in lower light intensities, but in very low intensity (5%) there was a higher number of abnormal seedlings. The 12 hours imbibition procedure was efficient to increase the process of germination, although there was no difference among treatments. Seeds collected in these three fragments (urban, periurban and rural) showed good potential for production of quality seedlings of J. micrantha.